Mapeamento dos aspectos afetivos que influenciam e dificultam a aprendizagem a partir do uso de ferramentas pedagógicas produzidas por egressos do mestrado profissional de ensino de ciências na Amazônia - Melo, Marlucia Ferreira (2012)
This research was central intention to map the emotional aspects that influence and hinder the learning from the use of pedagogical tools produced by graduates of the Master of Science Teaching Professional at Amazon. Thus proposed focus and guide the look in teacher student relations as ability to perform activities that contribute to improving the quality of learning from lessons mediated educational resource, especially Kit Dive Deeper. He sought to identify how the affective dimension is present in the classroom and the social representation that teachers and students attribute the same. The work is supported by authors such as Piaget, Wallon, Vygotsky, among others, who emphasize, even indirectly the theme of affectivity and its importance for learning at the same time point out that cognitive and affective go together. The methodology used was ethnographic study, which is included in the qualitative approach. Data collection took place from the transcript of the reports of the participants, observing their activities and their participation in the activities performed. Data analysis was based on the description and groupings of the answers given in the formal and informal dialogues. All activities were established with the central focus on the learning process as well as the contributions that teachers and students attach to affectivity as a driver of learning. This research can still see the need and importance of pedagogical mediation from educational tools, such as developed and used here by the Academic Master graduates of science education in the Amazon.